The Relation Tensile Strength And Flexibility Of Bamboo For Soil Stabilization - Khoiriya Latifah; Joko Siswanto; Bambang Supriyadi; Carsoni C (Universitas Islam Sultan Agung, 2021)
Bamboo is an abundant material and easily available in Indonesia. In addition to having high compressive strength and tensile strength as well as ease of obtaining and low prices, bamboo is a consideration and focus in developing in the world of construction today. In this study, bamboo is used for soil stabilization, where bamboo is used in the form of fibre. This research focuses on the strength properties of various types of bamboo. The focus is to investigate the relationship between the maximum tensile strength of bamboo and the flexibility of bamboo in soil stabilization. This is very important, because bamboo fibers used for soil stabilization rely on their tensile strength rather than their compressive strength. Thus, the optimum tensile strength and flexibility of bamboo must be of particular concern. From the results of the study of the tensile strength of two types of bamboo, namely Apus Bamboo and Java Bamboo, the Apus Bamboo results were found to have a higher tensile strength of 225.57 mpa with maximum flexibility of 19.99 mm and 43.76 mpa for tensile strength of Javanese Bamboo with a level of flexibility of 10.26 mm.